2020
DOI: 10.2196/21915
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 Pandemic on Obsessive-Compulsive Symptoms Among University Students: Prospective Cohort Survey Study

Abstract: Background The COVID-19 pandemic is associated with common mental health problems. However, evidence for the association between fear of COVID-19 and obsessive-compulsive disorder (OCD) is limited. Objective This study aimed to examine if fear of negative events affects Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) scores in the context of a COVID-19–fear-invoking environment. Methods All participants were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
101
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(116 citation statements)
references
References 31 publications
11
101
1
3
Order By: Relevance
“…It is worth noting, however, that perceptions of threat and danger, including exaggerated danger-related stress responses to COVID-19, do not necessarily indicate a specific obsessional response, which has been suggested to depend on more specific perceived self-related vulnerabilities ( Aardema, 2020 ; Aardema & Wong, 2020 ). Nonetheless, results support that these danger-related stress reactions are associated with an increase in symptoms among those with OCD ( Ji et al, 2020 ; Nissen et al, 2020 ; Yassa et al, 2020 ), likely through similar mechanisms by which symptoms may be exacerbated in non-clinical and other clinical populations ( Song, 2020 ; Montano & Acebes, 2020 ; Taylor et al, 2020a ; Taylor et al, 2020c ).…”
Section: Discussionmentioning
confidence: 65%
“…It is worth noting, however, that perceptions of threat and danger, including exaggerated danger-related stress responses to COVID-19, do not necessarily indicate a specific obsessional response, which has been suggested to depend on more specific perceived self-related vulnerabilities ( Aardema, 2020 ; Aardema & Wong, 2020 ). Nonetheless, results support that these danger-related stress reactions are associated with an increase in symptoms among those with OCD ( Ji et al, 2020 ; Nissen et al, 2020 ; Yassa et al, 2020 ), likely through similar mechanisms by which symptoms may be exacerbated in non-clinical and other clinical populations ( Song, 2020 ; Montano & Acebes, 2020 ; Taylor et al, 2020a ; Taylor et al, 2020c ).…”
Section: Discussionmentioning
confidence: 65%
“…This concurs with the recent findings of a Turkish study (Satici et al, 2020 ) which reported a significant role of fear of COVID-19 on life satisfaction via different psychological distress measures (i.e., depression, anxiety, and stress). Additionally, fear of COVID-19 has been reported to be a strong indicator of obsession and compulsion in the specific context of the COVID-19 pandemic (Ji et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…ASQ may be used in clinical and college settings to detect anxiety and depression. An essential screening tool for obsessive-compulsive disorder is the Yale Brown Obsessive Compulsive Scale, Y-BOCS, which can be part of the evaluation of patients with pre-existing obsessive-compulsive disorder, or for long-term follow up of anxiety resulting from COVID-19 infection (Davide et al 2020;Ji et al 2020).…”
Section: Screening For and Diagnosis Of Anxietymentioning
confidence: 99%